KAJIAN PENGENDALIAN HAMA PENGGEREK BATANG CENGKEH ( Hexamitodera semivelutina Hell. ) MENGGUNAKAN METABOLIT SEKUNDER JAMUR Metarhizium DAN Beauveria DENGAN METODE INFUS AKAR - Fini Natalia Tumewan; Jackson Watung; Maxi Lengkong; Dewi R. (COCOS, 2020)
SUMMARYThis research aims to determine the effectiveness of the use of secondarymetabolites of Metarhizium and Beauveria fungi by infusion of roots in clove plantsagainst H. semivelutina larvae. The results of the study are expected to benefitfarmers in controlling H. semivelutina pests with secondary metabolites of thefungus Metarhizium and Baeveria in clove plants by means of a root infusion.The study was conducted in a clove plantation area owned by farmers in TonsawangVillage, Tobatu District, Southeast Minahasa Regency, North Sulawesi. Theresearch lasted for 3 (three) months, from February to April 2020. This study useda Randomized Block Design (RBD) method on farmers' clove plants.Determination of plants that will be applied to the root infusion is done by lookingat plants that are attacked by H. semivelutina pests by looking at the hole that emitsliquid mixed with feces in the clove plants in Tonsawang Village, Tombatu District.In this study using secondary metabolites of Metarhizium fungus and Beauveriafungus in H. semivelutina pest control by means of root infusion.The results showed that the average effectiveness of the use of secondarymetabolites in controlling H. semivelutina reached 78.52%, with a percentage ofeffectiveness of the secondary metabolite of Metarhizium fungus at 81.05% whichwas not significantly different from the secondary metabolite of Beauveria that was75.59%, but significantly different from the control of 10.57 %.Keywords: Effectiveness, secondary Metarhizium metabolites of fungus,Beauveria, H. semivelutina, Tombatu.Keywords: Effectiveness, secondary metabolites of Metarhizium fungus,Beauveria, H. semivelutina, Tombatu.